PRACTICAL BASIS OF STUDYING SCIENTIFIC PEDAGOGICAL ASPECTS OF UZBEKISTAN FINE ART HERITAGE TRADITIONS - Umirov Karim (European International Journal of Pedagogics, 2024)
The educational process in the fine arts, along with the formation of students' skills in drawing, architecture, aesthetic perception of the beauty of the environment, the theoretical knowledge of its reflection on the basis of visual aids and develops skills. It should be noted that the teacher's approach and skills play an important role in achieving these goals.